AESTHETIC TRANSFORMATIONS OF BALINESE WAYANG PARWA AND RAMAYANA PERFORMANCES IN THE GLOBAL ERA - Marajaya, I Made; Surya Peradantha, Ida Bagus Gede (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2025)
Since the 1970s, Wayang Parwa and Wayang Ramayana performances in Bali have undergone significant aesthetic transformations in response to the currents of global culture. This study examines the forms and processes of these transformations, as well as their implications for the sustainability of Balinese shadow puppet theatre. The research employs a qualitative method, with data collected through observation, interviews, and documentation, and analyzed using theories of transformation, aesthetics, and creativity. Findings indicate that globalization has influenced Balinese puppeteers (dalang) to innovate various components of the performance, including musical accompaniment, lighting, the screen (kelir), the use of comedic puppets (bebondresan), the structure of the performance, and the overall style of presentation. These creative efforts have succeeded in attracting public interest back to the shadow puppet performances and have also spurred innovations in other types of wayang performances, such as Wayang Calonarang and Wayang Babad. The aesthetic transformation of Wayang Parwa and Wayang Ramayana performances has contributed significantly to the government, entrepreneurs, and society at large, as these performances are often utilized as a medium for communication and dissemination of information directly related to social life in the era of globalization.